(untitled) (Dhaka University Journal of Biological Sciences, 2023)
The problem of the present study was to investigate whether there is any effect of contextual cues on learning. Literature review indicated a lack of a reliable previous answer to the problem. The purpose of the study was to test whether any connection is created for contextual cues in the brain. It was hypothesized that each contextual cue creates a distinguished connection in the brain. If contextual cues remain identical throughout both practice and revision sessions, learning will enhance. Purposively drawing 36 students from class V, we randomly assigned them under two conditions, namely control and experimental groups. The results showed that the mean scores of control and experimental groups were 9.56 and 14.83 consecutively, which differ significantly at the p < .001 (t = -6.752) level. Since experimental group scored significantly higher than the control group, it was concluded that contextual cues play an important role on learning. Dhaka Univ. J. Biol. Sci. 31(2): 303-307, 2022 (July)